Mitigation of Voltage flicker and reduction in THD by using STATCOM - S. Chandrasekhar; J. Brahmmam; M. Srinu (Institute of Advanced Engineering and Science, 2013)
Voltage flicker is considered as one of the most severe power quality problems (especially in loads like electrical arc furnaces) and much attention has been paid to it lately. Due to the latest achievements in the semiconductors industry and consequently the emergence of the compensators based on voltage source converters, FACTS devices have been gradually noticed to be used for voltage flicker compensation. This paper covers the contrasting approaches; dealing with the voltage flicker mitigation in three stages and reduction in total harmonic distortion and assessing the related results in details. Initially, the voltage flicker mitigation, using FCTCR (Fixed Capacitor Thyristor Controlled Reactor), was simulated. Secondly, the compensation for the six-pulse as well as 12-pulse Static Synchronous Compensator (STATCOM) has been performed. In this case, injection of harmonics into the system caused some problems which were later overcome by using 12-pulse assignment of SATCOM and RLC filter (three phase harmonic filter). The obtained results show that STATCOM is very efficient and effective for the flicker compensation as well as harmonic sprectrum. All the simulations have been performed on the MATLAB Software.DOI:http://dx.doi.org/10.11591/ijece.v3i1.1951